Hubungan Jump Service dengan Risiko Jumpers Knee pada Pemain Bola Voli - Amanda, Tasya Ghea; Rahayu, Umi Budi (Universitas Baiturrahim, 2025)
Jump service is one of the techniques used by volleyball athletes. Jump service is carried out using a service technique accompanied by a sudden jump as high as possible or what is usually called explosive power. This is one of the triggers for knee pain or also known as Jumpers knee. The extent identify to which Jump Service is related to the risk of Jumpers Knee in volleyball players. This research method is an observational study using a jump service correlational approach (Independent variable) with the risk of jumpers knee (Dependent variable) for Tadifa Volleyball Club and Jambi City PBS VC Volleyball Club players, a sample of 61 using the total sampling method.. From the results of research conducted at the Jambi City Volleyball Club, it was found that the male respondents were 54.09% and the female respondents were 45.90%. Carrying out the Spearman-Rho correlation test, the significance result was 0.097 (>0.05), which means There is no relationship between jump service and jumpers knee in Jambi City Volleyball players. Patellar tendinopathy is a common injury that often occurs in sports that involve jumping, such as volleyball and basketball. Although this injury has a high prevalence among athletes in jumping sports, especially volleyball and basketball, this injury has big factors influencing the occurrence of jumpers knee, such as excessive body weight, weak patellar ligaments, stiffness of the hamstring muscles, trauma to the knee, poor angle of the foot. more and the length of the patella is not parallel.